Α-Tubulin Acetylation Restricts Axon Overbranching by Dampening Microtubule Plus-End Dynamics in Neurons. (5th September 2017) - Dan Wei,; Gao, Nannan; Li, Lei; Zhu, Jing-Xiang; Diao, Lei; Huang, Jiansong; Han, Qing-Jian; Wang, Shaogang; Xue, Huaqing; Wang, Qiong; Wu, Qing-Feng; Zhang, Xu; et al.
Abstract: Axon growth is tightly controlled to establish functional neural circuits during brain development. Despite the belief that cytoskeletal dynamics is critical for cell morphology, how microtubule acetylation regulates axon development in the mammalian central nervous system remains unclear. Here, we report that loss of α-tubulin acetylation by ablation of MEC-17 in mice predisposes neurons to axon overbranching and overgrowth. Introduction of MEC-17 F183A lacking α-tubulin acetyltransferase activity into MEC-17-deficient neurons failed to rescue axon defects. Moreover, loss of α-tubulin acetylation led to increases in microtubule debundling, microtubule invasion into filopodia and growth cones, and microtubule plus-end dynamics along the axon. Taxol application dampened microtubule hyperdynamics and suppressed axon overbranching and overgrowth in MEC-17-deficient neurons. Thus, our study reveals that α-tubulin acetylation acts as a brake for axon overbranching and overgrowth by dampening microtubule dynamics, providing insight into the role of microtubule post-translational modifications in regulating neural development.